2021
DOI: 10.2169/internalmedicine.5185-20
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ramucirumab in Patients with Unresectable Hepatocellular Carcinoma with Progression after Treatment with Lenvatinib

Abstract: Objective A survival benefit was demonstrated for ramucirumab (RAM) in patients with unresectable hepatocellular carcinoma (uHCC) and α-fetoprotein (AFP) concentrations ≥400 ng/mL who had previously received sorafenib (SOR). However, it is unclear whether RAM has a similar efficacy in patients with uHCC that progresses after lenvatinib (LEN) treatment. This study aimed to evaluate the early anti-tumor response to RAM as a second-line treatment for advanced uHCC after LEN treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The change in the AFP value after the start of ramucirumab was compared with the best response by mRECIST. It has already been reported that AFP reduction after TKIs, such as sorafenib and lenvatinib, may be useful for predicting treatment response [10-12], and similarly, Kasuya et al [13] reported that the rate of change in AFP may help predict efficacy even with ramucirumab. In the present study, disease control was obtained in 5 of 6 cases in which AFP decreased in the 1st month after the start of ramucirumab, whereas disease control was not obtained in 5 of 6 cases in which AFP continued to increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the AFP value after the start of ramucirumab was compared with the best response by mRECIST. It has already been reported that AFP reduction after TKIs, such as sorafenib and lenvatinib, may be useful for predicting treatment response [10-12], and similarly, Kasuya et al [13] reported that the rate of change in AFP may help predict efficacy even with ramucirumab. In the present study, disease control was obtained in 5 of 6 cases in which AFP decreased in the 1st month after the start of ramucirumab, whereas disease control was not obtained in 5 of 6 cases in which AFP continued to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Kuzuya et al [14] reported that the DCR was 80.0%, and the median time to progression (TTP) was 3.1 months. In addition, Kasuya et al [13] reported that the DCR was 28.6%, and median PFS was 41 days, and Hiraoka et al [15] reported that the DCR was 42.3% and the median TTP was 2.0 months.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study reported a disease control rate (DCR) of 60% in 10 patients who received ramucirumab treatment after lenvatinib [86]. Another retrospective study showed a DCR of 33% in six patients that were treated with ramucirumab after lenvatinib [87]. The populations of these two studies were too small to draw any definitive conclusions regarding the efficacy of ramucirumab treatment after lenvatinib failure.…”
Section: The Frequency and Predictive Factors Of Transition To Post-pmentioning
confidence: 99%
“… 26 In a smaller study, 7 patients with unresectable HCC and AFP ≥ 400 ng/mL and previously treated with lenvatinib, received ramucirumab and achieved a DCR of 28.6% and a mPFS of 41 days. 27 A recent similar study with a larger sample size (n = 28) reported a DCR of 42.3% and a mPFS of 2.0 months following failure of lenvatinib. 28 In a study by Hatanaka et al exploring the role of albumin-bilirubin score in predicting outcome of ramucirumab for treatment of patients with advanced HCC, the treatment response of 16 patients was reported: 29 DCR ranged between 28.6% and 100%, mOS ranged between 3.0 months and 6.7 months, and mPFS ranged between 1.4 and 7.5 months (depending on albumin-bilirubin score).…”
Section: Clinical Efficacy and Limitations Of Ramucirumabmentioning
confidence: 89%